P-I snake venom metalloproteinase is able to activate the complement system by direct cleavage of central components of the cascade. - Giselle Pidde-Queiroz; Fábio Carlos Magnoli; Fernanda C V Portaro; Solange M T Serrano; Aline Soriano Lopes; Adriana Franco Paes Leme; Carmen W van den Berg; Denise V Tambourgi (Public Library of Science (PLoS), 2013)
BACKGROUND: Snake Venom Metalloproteinases (SVMPs) are amongst the key enzymes that contribute to the high toxicity of snake venom. We have recently shown that snake venoms from the Bothrops genus activate the Complement system (C) by promoting direct cleavage of C-components and generating anaphylatoxins, thereby contributing to the pathology and spread of the venom. The aim of the present study was to isolate and characterize the C-activating protease from Bothrops pirajai venom. RESULTS: Using two gel-filtration chromatography steps, a metalloproteinase of 23 kDa that activates Complement was isolated from Bothrops pirajai venom. The mass spectrometric identification of this protein, named here as C-SVMP, revealed peptides that matched sequences from the P-I class of SVMPs. C-SVMP activated the alternative, classical and lectin C-pathways by cleaving the α-chain of C3, C4 and C5, thereby generating anaphylatoxins C3a, C4a and C5a. In vivo, C-SVMP induced consumption of murine complement components, most likely by activation of the pathways and/or by direct cleavage of C3, leading to a reduction of serum lytic activity. CONCLUSION: We show here that a P-I metalloproteinase from Bothrops pirajai snake venom activated the Complement system by direct cleavage of the central C-components, i.e., C3, C4 and C5, thereby generating biologically active fragments, such as anaphylatoxins, and by cleaving the C1-Inhibitor, which may affect Complement activation control. These results suggest that direct complement activation by SVMPs may play a role in the progression of symptoms that follow envenomation.